2017
DOI: 10.1186/s12985-017-0869-3
|View full text |Cite
|
Sign up to set email alerts
|

Marburg virus-like particles by co-expression of glycoprotein and matrix protein in insect cells induces immune responses in mice

Abstract: BackgroundMarburg virus (MARV) causes severe haemorrhagic fever in humans and nonhuman primates and has a high mortality rate. However, effective drugs or licensed vaccines are not currently available to control the outbreak and spread of this disease.MethodsIn this study, we generated MARV virus-like particles (VLPs) by co-expressing the glycoprotein (GP) and matrix protein (VP40) using the baculovirus expression system. MARV VLPs and three adjuvants, Poria cocos polysaccharide (PCP-II), poly(I:C) and alumini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…PCP, extracted from Poria cocos sclerotium, has been extensively studied as an immunomodulating agent [ 22 25 ]. According to previous reports, PCP significantly stimulated antibody responses, enhanced cytokines secretion and exerted protective role against MARV, rabies, and H1N1 [ 15 , 16 , 18 ]. To further elucidate that capacity of PCP to induce antigen-cross presentation and enhance cellular immune response, we used OVA as a model antigen in the present study.…”
Section: Discussionmentioning
confidence: 66%
“…PCP, extracted from Poria cocos sclerotium, has been extensively studied as an immunomodulating agent [ 22 25 ]. According to previous reports, PCP significantly stimulated antibody responses, enhanced cytokines secretion and exerted protective role against MARV, rabies, and H1N1 [ 15 , 16 , 18 ]. To further elucidate that capacity of PCP to induce antigen-cross presentation and enhance cellular immune response, we used OVA as a model antigen in the present study.…”
Section: Discussionmentioning
confidence: 66%
“…EBOV vaccines should simultaneously stimulate the specific humoral and cellular immunity essential for effective vaccination [52][53][54]. The protective cellular immune response is associated with the production of several cytokines, including IFN-γ, TNF-α, IL-2, IL-4, and IL-10 [10,55]. Our results showed that SBLP resulted in significant increases in the secretion of these cytokines and that these levels also significantly increased in the presence of the ISA 201VG plus Poly (I:C) adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…The Gai team successfully constructed a MARV virus-like particle (VLP). When Poria cocos polysaccharide PCP-II was combined with MARV VLP, the PCP-II group significantly enhanced the specific antibody response and neutralization antibody titer of MARV VLP and improved the immune level of mice [ 82 ]. The protective effect of PCP-II combined with MARV VLP was further evaluated in primate rhesus monkeys.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Vaccine adjuvant [82,83] Table 2. Antiviral activities of medicinal fungi and their mechanism of action in plant and animal viruses.…”
Section: Poria Cocosmentioning
confidence: 99%